Prescription Patterns in the Outpatient Unit of XYZ Hospital, Pekanbaru: A Study from 2022 - Iskandar, Benni; Tiara Tri Agustini; Mira Febrina; Rahmadhani; Rickha Octavia (Universitas Ahmad Dahlan, 2025)
This study aims to assess the rationality of drug prescribing practices in the Outpatient Department of XYZ Hospital Pekanbaru using the World Health Organization (WHO) prescribing indicators. The research is an observational study with a descriptive nature, employing systematic random sampling to analyze data extracted from prescription records in the pharmacy department of XYZ Hospital Pekanbaru. A total of 660 prescription samples were evaluated, revealing an average of 2.91 drugs prescribed per prescription sheet, indicating a lack of adherence to diagnostic considerations. The findings show that the percentage of generic drug prescriptions was 64.04%, while antibiotic prescriptions accounted for 32.57%. Additionally, prescriptions for injectable forms constituted 1.36%, and adherence to the national formulary was at 72.27%. Out of the five prescribing indicators assessed, only the prescribing of injectable forms met the WHO’s prescribing indicators standard. These results highlight the necessity for improved adherence to rational prescribing practices to enhance treatment efficacy, minimize adverse drug reactions, and ensure cost-effectiveness in patient care. Regular monitoring and education of healthcare providers regarding rational drug use principles are essential for improving healthcare service quality.